Mineralogy of the human brain: a review - G. P. Servetto; C. M. Root; R. Gieré; R. Gieré; R. Vigliaturo; R. Vigliaturo (European Journal of Mineralogy)
The human brain can both synthesize minerals in situ and accumulate exogenous phases from the surrounding environment. Some of the biogenic phases may represent evolutionary remains, whereas others are crucial for many physiological functions of the neurological system. Yet an excess concentration of these minerals in the brain may be a precursor and/or a consequence of several neurodegenerative conditions, such as Alzheimer's and Parkinson's diseases. In this regard, there is very little in the literature that is focused on the minerals and mineraloids present in the human brain and on their physicochemical state. The gap in the literature is particularly wide for nanoscale and sub-nanoscale compounds. This review compiles the most significant research on minerals and mineraloids in the brain, the related neurodegenerative diseases, and their relationship with urban pollution. Here, we describe the strong link between neurodegenerative diseases and the presence of biogenic and exogenous minerals and mineraloids. Additionally, we highlight the importance of medical mineralogy for investigating diseases related to such phases. Future research must focus on not only the mineralogical characterization of particles in the brain but also the alteration and transformation of these particles in specific media and different locations in human brain cells and tissues. Further studies should attempt to perform nanoscale to atomic-scale characterization of the structure, the surface, the valence state, and the electrical and magnetic fields of the particles of interest.